1999
DOI: 10.1590/s0100-879x1999000100001
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide: from toxin to endogenous modulator of cardiovascular functions

Abstract: Carbon monoxide (CO) is a pollutant commonly recognized for its toxicological attributes, including CNS and cardiovascular effects. But CO is also formed endogenously in mammalian tissues. Endogenously formed CO normally arises from heme degradation in a reaction catalyzed by heme oxygenase. While inhibitors of endogenous CO production can raise arterial pressure, heme loading can enhance CO production and lead to vasodepression. Both central and peripheral tissues possess heme oxygenases and generate CO from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
2
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 51 publications
3
60
2
1
Order By: Relevance
“…On the other hand, the antimechanical nociceptor hypersensitivity eect of NO does not depend upon CO release. These results are not at all in line with the literature, which suggests that CO inhibits NOS activity by inhibiting all NOS isoforms (Matsuoka et al, 1994;Sato et al, 1998;Johnson et al, 1999;Throup et al, 1999). However, recent evidence has supported the theory that the interaction between the NO and CO pathways is more intricate than envisaged, being not restricted only to the NOS and HO level.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…On the other hand, the antimechanical nociceptor hypersensitivity eect of NO does not depend upon CO release. These results are not at all in line with the literature, which suggests that CO inhibits NOS activity by inhibiting all NOS isoforms (Matsuoka et al, 1994;Sato et al, 1998;Johnson et al, 1999;Throup et al, 1999). However, recent evidence has supported the theory that the interaction between the NO and CO pathways is more intricate than envisaged, being not restricted only to the NOS and HO level.…”
Section: Discussioncontrasting
confidence: 47%
“…However, the notion that CO is only a poison has been challenged since 1949 when Sjostrand (1949) reported that CO could be endogenously synthesized, but it was not until 1991 that Marks et al (1991) assumed that CO could have a physiological function. Currently, CO is recognized as an important signalling molecule in cardiovascular system, being a vasoactive substance (Dawson & Snyder, 1994;Johnson et al, 1999) and reducing the expression of endothelin-1 in endothelial cells . CO has also been recognized to act as a neurotransmitter or neuromodulator in the nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, these heme-derived metabolites were considered toxic waste products, but accumulating data suggest they have anti-oxidative, antiinflammatory, antiapoptotic, and signaling properties and possibly immune modulatory functions. [31][32][33][34][35] Therefore, we postulate that, in vivo, large amounts of free heme exert inflammatory actions resulting in the expression of adhesion molecules and the recruitment of leukocytes, whereas HO down-regulates inflammation through a mechanism involving the down-modulation of adhesive properties. To examine this hypothesis, the roles of heme and HO as inflammatory modulators were investigated in a mouse model.…”
Section: Heme Oxygenase and Inflammationmentioning
confidence: 99%
“…Iron has been associated with the modulation of the metabolism and availability of certain chemical mediators such as nitric oxide (9)(10)(11) and carbon monoxide (12), which are implicated in baroreflex function both peripherally and centrally (13)(14)(15). Nitric oxide as well as oxygen-derived free radicals induced by changes in iron concentration are known to suppress baroreceptor activity particularly at high levels of arterial pressure (15).…”
Section: Introductionmentioning
confidence: 99%